Family resilience factors in conflict region - Mawarpury, Marty; Naidi Faisal, Naidi (Asosiasi Psikologi Islam (API) Himpsi, 2017)
Aceh is one of provinces in Indonesia exposed to traumatic events such as armed and politic conflict for decades until the Tsunami disaster in 2004. The impact is structural damage to the socio-culturaland society wellbeing. Most studies of the conflict are reviewed from pathological life experience perspective which managed individually, however some studies showed that experience in life may produce positive effect called resilience. Family resilience can occur in various contexts, but in the conflict context are still understudy, especially in Indonesia. The aim of this research was to identify determinant of family reselience in Aceh. The research used qualitative approach with case study method. Depth interview was conducted on three families with elligibility criteria i.e. had violence both personally and family member during conflict period 1998-2005, aged over 25 years, staying together with family and living in North Aceh. The result showed that factors affecting family resilience in conflict region consisted of religiosity, coping flexibility, social support, optimism and family structure. Furthermore, individual resilience in family contributed to family resilience in facing challenges and difficulties due to conflict. Keywords : Family Resilience, Conflict, Aceh